Psychometric properties of the Teruel Orthorexia Scale (TOS) among a French–Canadian adult sample - Maïano, Christophe (2022)
Background: Psychometric properties of the Teruel Orthorexia Scale (TOS) have been examined in several languages (Arabic, English, Portuguese, Spanish, and Turkish), but not in French. Purpose: The objective was to examine the psychometric properties of the TOS among a French-Canadian adult sample. Methods: Participants were 296 French-speaking Canadian adults (M = 34.2 years, SD = 11.9, 85.1% women). They completed the TOS alongside with several other measures (e.g., alcoholic consumption, cigarette smoking, disturbed eating attitudes and behaviors, frequency of physical activities, intuitive eating, vegetarian diet, and negative affect). Results: The results supported the a priori two-factor representation (orthorexia nervosa and healthy orthorexia) of the French version of the TOS and provided further support for the superiority of an exploratory structural equation modeling approach, relative to a confirmatory factor analytic approach. Furthermore, the results supported no differential item functioning as a function of respondents’ characteristics (age, body mass index, diagnosis of eating disorders, frequency of physical activities, gender, and vegetarian diet). Latent mean differences were found in healthy orthorexia and orthorexia nervosa factors as a function of respondents’ characteristics. Finally, significant correlations were found between TOS factors and convergent measures (alcohol consumption, cigarette smoking, disturbed eating attitudes and behaviors, intuitive eating, and negative affect). Conclusion: The present study confirmed that the French version of the TOS has satisfactory psychometric properties (i.e., factor validity and reliability, no differential item functioning, and convergent validity). Level of evidence: V, cross-sectional study.